Analisis Tingkat Kepuasan Pengunjung Taman Wisata Alam Batu Angus Kota Bitung - Dien, Yuliana Thalia; Kapantow, Gene Henfried Meyer; Rumagit, Grace Adonia Josefina (AGRI-SOSIOEKONOMI, 2024)
This research aims to analyze the level of satisfaction of visitors to the Batu Angus Nature Tourism Park, Bitung City. This research was carried out from March to May 2024. The data collection method used a sample survey method. Data collection techniques involve conducting direct interviews with visitors, and managers use questionnaires as a tool in data collection. The questionnaire contains several questions related to relevant research. The sampling method was by chance (accidental sampling) on ​​91 visitors to the Batu Angus Nature Tourism Park. The analytical method used was Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of the research show that the satisfaction level of visitors to the Batu Angus Nature Tourism Park, Bitung City, is 84.01 percent, which is included in the very satisfied category. There are several indicators that need to be improved, namely: environmental cleanliness, roads to tourist locations, suitability of food prices, availability of public toilets, availability of public transportation to tourist locations and distance to tourist locations from the city center.